2017
DOI: 10.2166/wst.2017.510
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic nitrogen removal in Bacillus sp. K5: involvement of a novel hydroxylamine oxidase

Abstract: An aerobic denitrifying bacterium isolated from a bio-trickling filter treating NOx, Bacillus sp. K5, is able to convert ammonium to nitrite, in which hydroxylamine oxidase (HAO) plays a critical role. In the present study, the performance for simultaneous nitrification and denitrification was investigated with batch experiments and an HAO was purified by an anion-exchange and gel-filtration chromatography from strain K5. The purified HAO's molecular mass was determined by SDS-PAGE and its activity by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Y16 (Zhang et al ., 2014) and Bacillus sp. K5 (Yang et al ., 2017). Results from these studies showed that the enzymes for hydroxylamine conversion from heterotrophic microbes differ significantly from those found in autotrophic ammonia oxidizers, but the consequences of these differences have not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Y16 (Zhang et al ., 2014) and Bacillus sp. K5 (Yang et al ., 2017). Results from these studies showed that the enzymes for hydroxylamine conversion from heterotrophic microbes differ significantly from those found in autotrophic ammonia oxidizers, but the consequences of these differences have not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Y16 and Bacillus sp. K5 was 0.31 ± 0.06 and 0.045 ± 0.003 U/mg, respectively . And the activity of HAO purified from anammox bacterium was 9.6 U/mg .…”
Section: Discussionmentioning
confidence: 95%
“…K5 and Acinetobacter sp. Y16 is 71 and 61 kDa monomer, respectively . Therefore, purification and further research of HAO from different heterotrophic nitrifiers are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria biomass was measured by determining the optical density at 600 nm (OD 600 ) using a spectrophotometer (TU-1800S, PERSEE, China) [32].…”
Section: Analysis Methodsmentioning
confidence: 99%